PWE-138 The incidence and management of cystic duct stones: the intra-operative cholangiogram is more than just a diagnostic tool. (28th May 2012) - Dave, R; Yeomans, N; Cockbain, A; Toogood, G
Abstract : Introduction: Use of the Intraoperative cholangiogram (IOC) was introduced by Mirizzi in 1931, who recommended its routine use. Currently, routine IOC during laparoscopic cholecystectomy (LC) remains a controversial issue. Unsuspected common bile duct (CBD) stones are reported in only between 2% and 3% of cases, whereas "post-cholecystectomy syndrome (PCS), " is reported in 10% - 40%. A potential cause of this is retained stones within the cystic duct (CD) remnant. We aimed to identify the intra-operative incidence of CD stones and the incidence of post-operative complications following routine IOC. Methods: We analysed a prospectively maintained database of all LC and routine IOC performed by the senior author. Since 7 April 2010, the incidence of CD stones/sludge was prospectively recorded—once the incision on the CD had been made, the CD and the CBD were "milked" in a retrograde fashion to remove any debris prior to introduction of the catheter for IOC. Impacted CD stones were crushed laproscopically. We also analysed the entire database prospectively collected since 1999 for the incidence of CBD stones. T-test (continuous) and Chi 2 (categorical) tests were used to analyse predictors of CD stones. Results: 248 LC with IOC had been recorded from 7 April 2010. In this cohort, the incidence of CD stones was 13% (N=33/248) and CD sludge was 6% (N=15/248). The presence of CD stones was not significantly associated with raised liver function tests (ALT>100, ALT>350) nor with pre-operative diagnoses of cholecystitis, pancreatitis, jaundice or cholangitis. Out of the 248 patients, 4% of patients presented with pain post operatively (N=11). <1% (N=2/248) presented with CBD stones post-operatively despite a negative IOC. No patients presented with pancreatitis or cholangitis post-operatively. In addition, out of a larger cohort of 1957 LC performed by the senior author, 4.5% of cases had CBD stones detected on IOC. Conclusion: The incidence of CD stones is not well reported in published literature—the data that exists is mainly following repeat cholecytectomy for PCS rather than intraoperative detection. PCS is widely reported and can cause a therapeutic and diagnostic challenge. The presence of stones in the CD or within a retained gall bladder remnant may be the cause of residual symptoms, but are difficult to diagnose. We propose that the IOC is not only a diagnostic tool for identification of CBD stones and to delineate anatomy, but also serves a therapeutic purpose, allowing "milking" of the CD to remove any stones/debris which in our cohort has resulted in low rates of post-operative pain. Competing interests: None declared.